Synopsis 2 : Theologies. - Cassel, Valerie; Degot, Ekaterina; Gromala, Diana; Kafetsi, Anna; Khripun, Sergei; Kreuger, Anders; Leleu, Nathalie; Lynn, Victoria; Marangopoulos, Aris; Martinez, Rosa; Miki, Akiko; Riboli, Diana; et al. (Athene : EMST (National Museum of Contemporary Art), 2002)
Alithinos, Dimitri ; Amer, Ghada ; Gromala, Diana ; Mori, Mariko ; Neshat, Shirin ; Rakauskaité, Eglé ; Sharir, Yacov ; Shutov, Sergey ; Spiliopoulos, Marios ; Toufic, Jalal ; Viola, Bill ; Wirkkala, Maaria ; Zakharov, Vadim
biog., bibliog.
Engels & Grieks
Synopsis 2 : Theologies, EMST (National Museum of Contemporary Art) Athens, October 15, 2002 to January 5, 2003
boek